Intraoperative experiments combined with gait analyses indicate that active state rather than passive dominates the spastic gracilis muscle's joint movement limiting effect in cerebral palsy - Cemre, S.Kaya; bilgili, fuat; akalan, ekin; Temelli, Yener; Ateş, Filiz; Yücesoy, Can A. (My University, 2019)
In cerebral palsy, spastic muscle's passive forces are considered to be high but have not been assessed directly. Although activated spastic muscle's force-joint angle relations were studied, this was independent of gait relevant joint positions. The aim was to test the following hypotheses intraoperatively: (i) spastic gracilis passive forces are high even in flexed knee positions, (ii) its active state forces attain high amplitudes within the gait relevant knee angle range, and (iii) increase with added activations of other muscles. METHODS: Isometric forces (seven children with cerebral palsy, gross motor function classification score = II) were measured during surgery from knee flexion to full extension, at hip angles of 45° and 20° and in four conditions: (I) passive state, after gracilis was stimulated (II) alone, (III) simultaneously with its synergists, and (IV) also with an antagonist. FINDINGS: Directly measured peak passive force of spastic gracilis was only a certain fraction of the peak active state forces (maximally 26%) measured in condition II. Conditions III and IV caused gracilis forces to increase (for hip angle = 45°, by 32.8% and 71.9%, and for hip angle = 20°, by 24.5% and 45.1%, respectively). Gait analyses indicated that intraoperative data for knee angles 61-17° and 33-0° (for hip angles 45° and 20°, respectively) are particularly relevant, where active state force approximates its peak values. INTERPRETATION: Active state muscular mechanics, rather than passive, of spastic gracilis present a capacity to limit joint movement. The findings can be highly relevant for diagnosis and orthopaedic surgery in individuals with cerebral palsy.
Keywords: Cerebral Palsy; Epimuscular Myofascial Force Transmission; Gait Analysis; Intermuscular Mechanical Interactions; Muscle Force-knee Angle Characteristics; Spastic Muscle